Optimization of chemical transesterification of palm oil using response surface methodology - HARYATI, T.; MAN, Y.B. CHE; JINAP, S.; GHAZALI, H.M.; BUANA, L. (Blackwell Publishing, 1999)
The effect of catalyst concentration (0.1-0.5% methoxide powder), temperature (50-92C), and time (30-480 min) of chemical transesterification was studied to determine the optimum condition for maximizing concentration of triunsaturated and trisaturated triacylglycerols (TG) in palm oil. TG compositions of the oil were analysed using high-performance liquid chromatography. The optimum condition of the process was determined using statistical response surface methodology. The results showed that the triunsaturated and trisaturated TG responses followed a second order form of the treatments with R2 = 0.83 and 0.85, respectively. The triunsaturated TG reached a maximum concentration by using 0.36% catalyst at 78C and 360 min reaction time, whereas the trisaturated TG with 0.36% catalyst at 81C and 325 min reaction time. Considering the two responses, it was concluded that the overall optimum condition could be achieved at 0.36% of catalyst at 78-81C and 325-360 min reaction time. Such conditions increased trisaturated TG in palm oil by 2.34 times and triunsaturated TG by 1.54 times.